Association Between Residential Greenness and Cardiovascular Disease Risk. Issue 24 (18th December 2018) - Yeager, Ray; Riggs, Daniel W.; DeJarnett, Natasha; Tollerud, David J.; Wilson, Jeffrey; Conklin, Daniel J.; O'Toole, Timothy E.; McCracken, James; Lorkiewicz, Pawel; Xie, Zhengzhi; Zafar, Nagma; Krishnasamy, Sathya S.; et al.
Abstract : Background: Exposure to green vegetation has been linked to positive health, but the pathophysiological processes affected by exposure to vegetation remain unclear. To study the relationship between greenness and cardiovascular disease, we examined the association between residential greenness and biomarkers of cardiovascular injury and disease risk in susceptible individuals. Methods and Results: In this cross‐sectional study of 408 individuals recruited from a preventive cardiology clinic, we measured biomarkers of cardiovascular injury and risk in participant blood and urine. We estimated greenness from satellite‐derived normalized difference vegetation index (NDVI) in zones with radii of 250 m and 1 km surrounding the participants' residences. We used generalized estimating equations to examine associations between greenness and cardiovascular disease biomarkers. We adjusted for residential clustering, demographic, clinical, and environmental variables. In fully adjusted models, contemporaneous NDVI within 250 m of participant residence was inversely associated with urinary levels of epinephrine (−6.9%; 95% confidence interval, −11.5, −2.0/0.1 NDVI) and F2‐isoprostane (−9.0%; 95% confidence interval, −15.1, −2.5/0.1 NDVI). We found stronger associations between NDVI and urinary epinephrine in women, those not on β‐blockers, and those who had not previously experienced a myocardial infarction. Of the 15 subtypes of circulating angiogenic cells examined, 11 were inversely associated (8.0–15.6% decrease/0.1 NDVI), whereas 2 were positively associated (37.6–45.8% increase/0.1 NDVI) with contemporaneous NDVI. Conclusions: Independent of age, sex, race, smoking status, neighborhood deprivation, statin use, and roadway exposure, residential greenness is associated with lower levels of sympathetic activation, reduced oxidative stress, and higher angiogenic capacity.